The Indian subcontinent - Lahiri, A; Kennard, HJ (Oxford University Press, 2021)
This chapter provides brief descriptions of the basic intonational tunes and phrasing properties of some of the Indo-Aryan languages, including Bengali, Marathi, and Assamese, and also touches upon Dravidian languages such as Tamil and Telugu. The crucial issues governing the basic morphology of TUNES include the expression of focus, question prosody, the possibilities of neutral prosody, and phrasing, including its role in the expression of focus. One of the crucial cross-linguistic issues that is addressed relates to the presence or absence of H toned pitch accents and boundary tones related to questions. Some Indian languages show a mixture of H and L tones as well as critical phrasing patterns which suggest that phrasing may play a bigger role than one might be led to think on the basis of other Indo-European prosodic systems.